Scalable nanomanufacturing of holey graphene via chemical etching: an investigation into process mechanisms. Issue 12 (11th March 2022) - Bi, Kun; Wang, Dini; Dai, Rui; Liu, Lei; Wang, Yan; Lu, Yongfeng; Liao, Yiliang; Ding, Ling; Zhuang, Houlong; Nian, Qiong
Abstract : Partial reduction of graphene oxide results in vacancy defects. The growth of these atomic vacancies to nanosized holes under peroxide etching is studied for efficient holey graphene manufacturing. Abstract : Graphene with in-plane nanoholes, named holey graphene, shows great potential in electrochemical applications due to its fast mass transport and improved electrochemical activity. Scalable nanomanufacturing of holey graphene is generally based on chemical etching using hydrogen peroxide to form through-the-thickness nanoholes on the basal plane of graphene. In this study, we probe into the fundamental mechanisms of nanohole formation under peroxide etching via an integrated experimental and computational effort. The research results show that the growth of nanoholes during the etching of graphene oxide is achieved by a three-stage reduction–oxidation–reduction procedure. First, it is demonstrated that vacancy defects are formed via a partial reduction-based pretreatment. Second, hydrogen peroxide reacts preferentially with the edge-sites of defect areas on graphene oxide sheets, leading to the formation of various oxygen-containing functional groups. Third, the carbon atoms around the defects are removed along with the neighboring carbon atoms via reduction. By advancing the understanding of process mechanisms, we further demonstrate an improved nanomanufacturing strategy, in which graphene oxide with a high density of defects is introduced for peroxide etching, leading to enhanced nanohole formation.